STUDY OF SHORELINE CHANGE OF TABUHAN ISLAND IN WONGSOREJO DISTRICT BANYUWANGI REGENCY USING GOOGLE EARTH IMAGE - Rizqiyanto, Firdaus Achmad; Mauludiyah, Mauludiyah; Maisaroh, Dian Sari (Jurnal Segara, 2024)
The beach is an area that often experiences changes in shape that can occur quickly or slowly depending on those who influence it, both due to natural and artificial factors. Tabuhan Island is one of the islands that has the problem of shoreline changes. This study aims to determine the physical conditions of hydrooceanography and changes in the coastline of Tabuhan Island. Hydrooceanographic physical parameters include tides, currents, winds, waves and Total Suspended Solids (TSS). The study of changes in the coastline of Tabuhan Island uses the overlay method using Google Earth images in 2006, 2011, 2016 and 2021. The overlay method is a method of overlapping images from the old to the newest. The results show the waters of Tabuhan Island have a mixed tidal type with a double daily trend, the current speed ranges from 0.2760 m/s to 0.9023 m/s from north to south and the wind has a speed of 0-17 knots dominantly from south to north and southeast to northwest. The waves have a maximum height of 2.6 m and a minimum of 0.01 m and the highest Total Suspended Solid (TSS) value is 198.9 mg/L and a minimum of 110.3 mg/L. The results of the study show the area Tabuhan Island has reduced its area from 67,313.4 m² to 50,028 m²mwith an annual evenly of 850.9 m² in the period 2006 – 2021. The abrasion value that occurs is 22,423.3 m² happening in south and west and the accretion is 5,128.9 m² happening in the north Tabuhan Islands.